The Effectiveness Of Kepok Banana ( Musa Paradisiaca. L) Consumption On Reducing First Trimester Igravidarum Emesis - Meirita Herawati; Lisviarose; Uli Arta (Institute of Computer Science (IOCS), 2022)
Emesis gravidarum is a complaint that often occurs in pregnant women, especially in the first trimester. In addition to pharmacological drugs, emesis gravidarum can also be treated non-pharmacologically. This study aims to determine the effectiveness of the consumption of kepok bananas (Musa Paradisiaca Formatypica) on the reduction of first trimester emesis gravidarum in the Independent Midwife Practice (PMB) Susanti Pekanbaru City. The study was conducted from June to August 2021. The type of research used was pre-experimental with a one-group pre-post-test design which did not use a control group, but previously the group had pretest observations so that researchers could compare changes. The population of this study was 15 respondents. The sampling technique in this study was total sampling. The research instrument is a questionnaire sheet and bivariate data analysis. From the results of the study, it is known that the average emesis gravidarum before consuming banana kepok is 9.27 and the average emesis gravidarum after consuming banana kepok is 7.00. The results of the paired T-test showed the effectiveness of kepok banana consumption on decreasing first trimester emesis gravidarum with p value 0.000 < 0.05. From the results of this study, it is expected that pregnant women who experience emesis gravidarum can consume kepok bananas boiled for 40 minutes 3 times a day. Researchers suggest to health workers to be able to provide education about the benefits of kepok bananas to pregnant women in the first time who experience emesis gravidarum.